Engagement e conteúdo em vídeos sobre a aplicação de online dating Tinder no YouTube - Sepúlveda, R. (2021)
Online dating solutions have diversified and increased in the number of users, mainly powered by mobile applications. Among them, Tinder has drawn the attention of the generalist press and academia due to a set of distinctive attributes that have posited several questions. This research proposes a methodological approach to understand what narrations related to the application and its users are disseminated on YouTube, an essential platform for spreading narratives about various topics and sharing content. A quantitative and qualitative analysis of the most influential YouTube videos on Tinder was carried out using digital methods. The results show that they portrayed the online dating stages, such as creating a profile, matching, and meeting, reflecting on and upholding the controversies associated with the application. The creation of videos was primarily driven by curiosity about Tinder and the need to provide appealing content to the audience.